(untitled) (Prostor, 2025)
The unrealized Technical Campus project on Zagreb’s eastern outskirts was envisioned as a key driver of the city’s industrialization, with funding allocated as part of the economic framework of the First Five-Year Plan. This ambitious complex was designed to train technically educated professionals, with the Directive Regulatory Plan allocating the eastern parts of the city for its development and expansion. However, just two years after its initial conception, the project faced obstacles that delayed its phased implementation and ultimately halted construction. This paper explores the evolving role of engineers within the existing model of technical education, emphasizing a blend of theoretical and practical training. It also examines the procedures, organizational structures of urban planning authorities, and the highly educated professionals involved - whose work was often uncoordinated, with decisions frequently revised or deferred. By analyzing the spatial and programmatic aspects of the Technical Campus, the study seeks to highlight how planning this peripheral urban enclave as a fragment prefigures the broader strategy: a smaller-scale embodiment of a larger spatial framework that demonstrated notable resilience despite the ongoing regulatory shifts and administrative reorganizations characteristic of the early postwar period.